The making of a grand champion steer - Ireland, Harry A. (My University, 1907)
Introduction: In the begining of the discussion of this subject it will be well to have the term "grand champion" defined as it is meant here. The expression is a show ring term and applies to the animal of any age or breed, that has won first honors in his class, championship over all animals of his age and grandchampionship over all breeds and ages. Most of the larger fairs have classes made up of the champions of different ages from the first prize winners, so that in a season there may be numerous so called grandchampions of every degree of merit, but the term "grandchampion steer" as used here shall be taken as applying only to the winner over all animals of similar nature, of any breed or age, at the world's greatest live stock exposition, "The Chicago International",held annaulIy at the Union Stock Yards of Chicago, Illinois. The entire live stock world is represented at this great exposition and each year produces but one grandchampion beef animal, hence it is easily understood how keen, almost bitter, among breeders and feeders is the competition for the coveted honor of having bred or fitted the animal that for the time is the center of attraction in the cattleman's world. It is hardly necessary to describe the grandchampion here indeed it is hardly possible to say what distinguishes him from the other champions because the contest is often so close that the most expert judge can scarcely choose between them. The grandchampion steer is simply the highest type of beef animal that the best skill and highest intelligence in breeding and feeding can produce. He must have sufficient size for his age, neither of which, however, are strictly defined, the greatest possible amount of flesh of the highest possible quality. He may be of any breed or of no breed or of any color. Such points as the latter are supposed to have no influence in the choice of a grandchampion, although personal preference in regard to color and breed, especially the latter, may sometimes be a judges only means of deciding between two animals.
Citation: Ireland, Harry A. The making of a grand champion steer. Senior thesis, Kansas State Agricultural College, 1907.
Morse Department of Special Collections
Keywords: Livestock Exhibition; Steers; Competitions; Theses